The intracellular carboxyl terminal domain of Vangl proteins contains plasma membrane targeting signals. (10th March 2014) - Iliescu, Alexandra; Gros, Philippe
Abstract Vangl1 and Vangl2 are integral membrane proteins that play a critical role in establishing planar cell polarity (PCP) in epithelial cells and are required for convergent extension (CE) movements during embryogenesis. Their proper targeting to the plasma membrane (PM) is required for function. We created discrete deletions at the amino and carboxy termini of Vangl1 and monitored the effect of the mutations on PM targeting in Madin–Darby canine kidney cells. Our results show that the Vangl1 amino terminus lacks PM targeting determinants, and these are restricted to the carboxy terminus, including the predicted PDZBM motif at the C‐terminus.